The Figurative Language in David Campbell’s Poem “Night Sowing” and Their Translation into “Menyemai di Malam Hari” - Juliarta, I Made; Wirawan, I Gede Nika (Al-Lisan: Jurnal Bahasa, 2021)
This study aims to find out the types of figurative language found in David Campbell’s poem “Night Sowing” and their translation “Menyemai di Malam Hari” and to find out the meanings of the figurative language found in David Campbell’s poem “Night Sowing” and their translation “Menyemai di Malam Hari”. This study used the theory proposed by Larson (1998:121). In collecting data, this study used the library research method, and the data were collected in some steps to obtain appropriate and sufficient data. The steps in getting the data of this writing were done by reading attentively and accurately with the focus on the figurative languages in the poem. The result of study revealed that metonymy, idiom and personification are the types of figurative languages found in the data source. In translating the idiomatic expression, it needs the proper strategy so that the meaning in the source language can still be maintained.